Fototerapija in fotokemoterapija v dermatologiji - Zagoričnik, Blanka (Medicinski razgledi, 2001)
The beneficial effect of ultraviolet (UV) radiation on the course of some skindiseases is well known for a long time. The progress in technology and development of irradiation units that radiate UV-rays of special wave-length increased the possibility of phototherapy. Phototherapy as a method of treatment in dermatology has become widely used because of its relative safetyand simplicity in comparison with photochemotherapy which is used only in specialized centres. In addition the paper discusses different kinds of treatment with UV radiation.
Keywords: Koža, bolezni; Skin diseases; Therapy; PUVA zdravljenje; Ultravijolična terapija; Ultraviolet therapy; dermatologija; Puva therapy; kožne bolezni; zdravljenje; fototerapija